Informativeness of Experiments for MEU - A Recursive Definition - Daniel Heyen; Boris R. Wiesenfarth (University of Heidelberg, Department of Economics, 2014)
The well-known Blackwell's theorem states the equivalence of statistical informativeness and economic valuableness. Celen (2012) generalizes this theorem, which is well-known for subjective expected utility (SEU), to maxmin expected utility (MEU) preferences. We demonstrate that the underlying definition of the value of information used in Celen (2012) is in contradiction with the principle of recursively defined utility. As a consequence, Celen's framework features dynamic inconsistency. Our main contribution consists in the definition of a value of information for MEU preferences that is compatible with recursive utility and thus respects dynamic consistency.
urn:nbn:de:bsz:16-heidok-175115
Keywords: 330; Value of information; Maxmin expected utility; Recursive utility